Choice of Aspiration Prevention Surgery for Patients With Neuromuscular Disorders: Report of Three Cases - Katoh, Mitsuhiko; Ueha, Rumi; Sato, Taku; Sugasawa, Shunichi; Goto, Takao; Yamauchi, Akihito; Yamasoba, Tatsuya (Frontiers in Surgery, 2019)
Dysphagia, one of the major complications of neuromuscular diseases such as Parkinson’s disease and amyotrophic lateral sclerosis, decreases quality of life and may lead to malnutrition or aspiration pneumonia. Although recent reports have suggested that surgical aspiration prevention improves quality of life and enables oral intake, the selection of appropriate aspiration prevention techniques has rarely been discussed. In this report, we present the cases of three patients with neuromuscular diseases who underwent surgical aspiration prevention; we selected the surgical techniques based on analysis of the dysphagia mechanisms, disease progression, and general condition in each case. Case 1 was a 55-year-old man with multiple system atrophy and presented with dysphagia associated with insufficient upper esophageal sphincter relaxation. We performed central-part laryngectomy, which was able to improve upper esophageal sphincter relaxation. Case 2 was a 79-year-old man with progressive supranuclear palsy who presented with respiratory disorder and dysphagia. Glottic closure under local anesthesia was selected because he also had acute hepatobiliary dysfunction and methicillin-resistant Staphylococcus aureus pneumonia with pleural effusion. Case 3 was a 75-year-old man with amyotrophic lateral sclerosis and presented with respiratory disorder and mild dysphagia. Subglottic closure with total cricoidectomy was selected because his dysphagia was expected to progress due to tracheostomy and disease progression. We also summarize the characteristics of the aspiration prevention surgical techniques based on our cases and on literature review. The causes of dysphagia, including insufficient upper esophageal sphincter opening during swallowing, weak pharyngeal constriction, velopharyngeal insufficiency, and inadequate laryngeal elevation, should be assessed by detailed examination before surgery, and the type of aspiration prevention surgery should be selected based on patient swallowing function and general condition.